Pengembangan Usulan Proses Bisnis Terintegrasi Produk Air Minum Ciryo dengan Konsep Business Process Reengineering Di CV. Titian Mandiri - Sutopo, Wahyudi; Hisjam, Muh.; Marhana, Laily (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2006)
CV. Titian Mandiri is an in-package drinking water manufacturer with brand name “Ciryo” locating in Karanganyar. The presence of problem indication results in inefficiency of proceeding business process, particularly in business process flow of production, warehouse, shipment, marketing, and financial divisions. This makes an analysis and evaluation on business process performance and integrated business process redesign conducted so that the company performance will be optimum. This study began with mapping business process in the form of flow diagram for identifying the company’s business activities. Then performance measurement was conducted based on model developed by Beamon (1999). This model analyzes three measurement variables: resource, process and output for finding out the factors resulting in inefficiency of the business process. Performance improvement was conducted by redesigning the business process procedure based on concept Business Process Reengineering. Basic steps of BPR involves rethink, redesign and retool. Standardization of the resulting business process based on cross-divisional activities interrelationship involves marketing, production, logistic, and financial modules. Based on redesign as a proposal for dealing with performance inhibition, it is used an integrated business process design for each module developed.